A high linearity low-noise amplifier in 0.25 μm BiCMOS Qubic4x for GSM application. (2nd January 2020) - Al Khoury, Michel; Jarry, Bernard; Barelaud, Bruno; Lintignat, Julien
ABSTRACT: In this paper, a low-noise amplifier (LNA) in 0.25 μm BiCMOS Qubic4x technology for Global System for Mobile communications (GSM) application is presented. The LNA uses inductive source degeneration to achieve noise and power gain matching simultaneously and parallel RC feedback to improve linearity. The LNA provides a forward gain (S21) of 10.3 dB with noise figure (NF) of 1.5 dB while drawing 50.6 mW power from a 1.6 V voltage supply. The simulated 1-dB compression point is 0 dBm at 942 MHz. The simulations are done in cadence virtuoso Spectre RF using 0.25 μm BiCMOS Qubic4x technology.